Corpo Devir: as afecções de uma mãetriz e palhaça - CRUZ, Paula Adrianna Barros da (2023)
This is a creative process in art. It is born in a movement of observation of the affections crossed in my body, from, of the maternity and of my life that permeates the University and the Theater. In a dialectic with my BEING and with thinkers of the Theater Language like Augusto Boal (1931-2009) and Antonin Artaud (1896-1948) who are my "support network" in thinking the scene of my body and making the scene with the Theater and education. And, in line with the trajectory of this body towards the encounter and discovery of the Self, I meet with the thinkers Gilles Deleuze (1925-1975) and Benedicto de Espinosa (1632-1677) about the states of affection of these bodies EU: mother, actress and clown . In this way, discovering the action in writing and in the media of life that exists me. The objective of this research is to report my maternal experience in letter formats, where a new cycle of construction begins over me, for the person I was, who I am and the relationships I have built in this space of the Theater with motherhood. The method used arose from the encounter I had with the first pregnancy, because the relationship between motherhood and theatrical language, together with the need to involve the “Body in Construction” in research that could contribute to the relationships between the states of my body's conditions with the world. The materials used were letters and videos, which are the fulfillment of my desire to become an educator on the human condition that the Theater has been expressing and living for centuries. The demonstration of the experience portrays the body / mother with the clownery, in which it was built through scenes and letters, providing encounters with other bodies, allowing to be affected with Theater. The sensations and experiences of the body under construction that is “me”, parallel to the thinkers and makers of this art, reinforces the course of the Body / Becoming, in which it emphasizes that I am like a newborn child who, from the first moment of his generation, goes receiving the external stimuli and giving its synapses “light”. Considering the proper approximations of my maternal experience in letter formats, I narrated the construction about me, more specifically the relationships that I have built in this space of the Theater with motherhood. Conclude that the Body is part of our daily lives and motherhood becomes a world from the moment I discover that a being grows inside me. Fortifying the true nature of the “Body in Construction” together with the living parts you build.